2022
DOI: 10.1155/2022/3305400
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Traffic Congestion Management in Smart Cities under Bidirectional Long and Short-Term Memory Model

Abstract: To solve the increasingly serious traffic congestion and reduce traffic pressure, the bidirectional long and short-term memory (BiLSTM) algorithm is adopted to the traffic flow prediction. Firstly, a BiLSTM-based urban road short-term traffic state algorithm network is established based on the collected road traffic flow data, and then the internal memory unit structure of the network is optimized. After training and optimization, it becomes a high-quality prediction model. Then, the experimental simulation ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…ereby, a high-quality prediction model is built. It is found that the prediction results of LSTM and BiLSTM are consistent with the actual traffic flow trend [27]. Based on its superior prediction characteristics, this paper also takes LSTM as one of the research methods.…”
Section: Marketing Model Based On Recurrent Neural Network (Rnn)mentioning
confidence: 60%
“…ereby, a high-quality prediction model is built. It is found that the prediction results of LSTM and BiLSTM are consistent with the actual traffic flow trend [27]. Based on its superior prediction characteristics, this paper also takes LSTM as one of the research methods.…”
Section: Marketing Model Based On Recurrent Neural Network (Rnn)mentioning
confidence: 60%
“…Abduljabbar et al (2021) [36] used the Bi-LSTM model for short-term traffic prediction on three different highways. Zhai et al (2022) [37] utilized the Bi-LSTM model to predict the short-term traffic flow on urban roads, and the prediction experimental results showed that the prediction accuracy of the Bi-LSTM model is higher than that of the single LSTM model. The Bi-LSTM model extracts the forward and backward features of time-series data at the same time, which causes the model to have better prediction results than the traditional LSTM model when dealing with strongly periodic time-series data [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth noting that in recent academic research, the Bidirectional Long Short-Term Memory (BILSTM) architecture has garnered Each RSU hosts the "Real-Time Vehicle Speed Calculation" module, which estimates the average vehicle speed as the autonomous vehicle progresses through the managed segments within specific time intervals. It is worth noting that in recent academic research, the Bidirectional Long Short-Term Memory (BILSTM) architecture has garnered significant attention for its effectiveness in predicting vehicle traffic flow across various road segments, as highlighted in previous studies [29][30][31][32]. Given the substantial impact of traffic flow patterns on the driving speed of autonomous vehicles, this module utilizes the BILSTM model introduced in [27] to compute the average vehicle speed.…”
Section: Autonomous Vehiclementioning
confidence: 99%